7.1: Invited Paper: Progress in Luminous Array Film (LAFi) with Plasma Tube Technology for Seamless Tilling Super‐large‐area Display. Issue 1 (1st July 2013) - Kosako, Terukazu; Guo, Bingang; Tanaka, Hajime; Hirakawa, Hitoshi; Awamoto, Kenji; Shinoda, Tsutae
Abstract A newly developed flat sealing process for glass tube edge provided a minimal seam by overlapped connection with transparent tube edge. Using these new techniques, we produced a new model of free expandable 1m × 2m stand‐alone display module that will provide a free designed curved super‐large area display.